Participation et développement soutenable des territoires - Alban Mannisi (Projets de Paysage)
Following the confusion of civil societies due to their loss of confidence in politics and planning experts, those involved in landscape construction have since implemented procedures to establish complex protocols of projects closer to the needs of residents of invested spaces. In a contemporary Japan, where the brutality of planning has changed the relationship with nature, we will report the experience of the philosopher Kuwako Toshio. Engage with territorial Planning issues, he develops methods of environmental mediation to better connect people to their environment.